2002
DOI: 10.1038/sj.bmt.1703386
|View full text |Cite
|
Sign up to set email alerts
|

Progressive interstitial fibrosis of the lung in sclerodermoid chronic graft-versus-host disease

Abstract: Summary:Sclerodermoid chronic graft-versus-host disease (sGVHD) is a well-known complication in patients with a long history of chronic GVHD. Pulmonary involvement in chronic GVHD presents typically as bronchiolitis obliterans (BO). Pulmonary fibrosis after allogeneic hematopoietic stem cell transplantation (HSCT) is presumed to be caused by the long-term toxicity of the conditioning regimen or the result of lung injury elicited predominantly by viral infections or GVHD. We present two patients with late onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 17 publications
1
26
0
2
Order By: Relevance
“…[6][7][8][9][10] The chance of recurrence suggests that bilateral pneumothoraces are more likely to occur metachronously than simultaneously. An important feature of these pneumothoraces is that they tend to be small or at most moderate in size, such that patients are asymptomatic or have only mild symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10] The chance of recurrence suggests that bilateral pneumothoraces are more likely to occur metachronously than simultaneously. An important feature of these pneumothoraces is that they tend to be small or at most moderate in size, such that patients are asymptomatic or have only mild symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, one patient who developed pneumothorax as a complication of OB after BMT without evidence of multiple bullae has previously been reported. 9 OB occurs more often after allogeneic BMTs, and its pathogenesis is complex and multifactorial, though most cases are though to be secondary to bronchial mucosal damage from GVHD with inflammation of the small airways and their subsequent obliteration. In most cases, OB after BMT develops within a few years after transplantation, but its diagnosis is not always straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies in children and adults showed a strong association between LONIPCs and chronic GVHD. [2][3][4][5][6][7] These studies focused on patients reinfused mostly with marrow progenitors from HLA-identical sibling donors. Since the incidence of chronic GVHD may be increased by the disparity of HLA matching and by the use of peripheral blood stem cells, 8,9 which have largely replaced bone marrow because of their relative ease of collection and the quicker engraftment kinetics, it may be hypothesized that LONIPC associated with GVHD is enhanced in the unrelated setting.…”
mentioning
confidence: 99%
“…Le scanner thoracique montre des images variées. Le LBA retrouve le plus souvent une alvéolite lymphocytaire et la biopsie pulmonaire des lésions de DAD, de pneumopathie interstitielle non spécifique, de LIP ou de fibrose évoluée avec infiltrat interstitiel lymphocytaire [43,50].…”
Section: Autres Pneumopathies Infiltrantes Diffusesunclassified